The Long Goodbye. Politics and economy in the crisis of the entrepreneurial State. Issue 1 (1st January 2020) - Guiso, Andrea
ABSTRACT: The article deals with the tight correlation between the decline of the 'Republic of parties' and the structural transformations of the global economy happening between the late sixties and the seventies in the spheres of monetary policy, international finance, and industrial organization. The crisis of the bond between politics and the mixed economy system planned in the 1930s is read as the story of a 'long goodbye' destined to end, after over twenty years, with the inversion of the traditional relationship whereby the economic power was submitted to the political power. The analysis is focused on three fundamental points: the evolution of the relations between Treasury and the Bank of Italy, the crisis of the system of industrial relations, and the major challenge of a new banking system.